A new species of Stigmatodactylus (Orchidaceous) from Sabah, Malaysian Borneo - Siti Fatimah Md.-Isa; Vanielie Terrence Justine; Alastair S. Robinson (Magnolia Press, 2025)
Stigmatodactylus Maksimowicz in Makino (1891: 81) is a small genus of orchids in subtribe Acanthine (Schlechter 1911: 384) with 28 accepted species (POWO 2024). The genus ranges from the eastern Himalayas and Japan southeast across the Sunda Shelf and Papu Asia to New Caledonia (Kores 1991, Robinson 2016) but is frequently overlooked in the wild since most species are diminutive and cryptic in the vegetative state. The genus is related to the better-known Cory bas Salisbury (1807: t. 83), the helmet orchids, which it resembles in the sterile state, comprising a single leaf. However, in its fertile state it produces one to few more conventionally structured flowers on an erect raceme, each flower subtended by a leafy bract, and resembles the closely allied and morphologically similar Acanthus Brown (1810: 321) from which several Stigmatodactylus species have been previously transferred (Clements & Jones 2018, Kores 1992). Two Stigmatodactylus species (Table 1) are currently recognized from Malaysia: S. lamrii (Wood & Chan, 1993: 274) Jones & Clements (2002: 441) and S. richardia us Ong in Ong & Tan (2015: 73). Stigmatodactylus lamrii is endemic to Mount Kinabalu, where it has been collected from the Pinosuk Plateau (Wood et al. 2011), whereas S. Richardean us was described from northern Kedah in Peninsular Malaysia (Ong & Tan 2015). During the Sabah Parks Marai Parai–Gurkha Hut 2023 Scientific Expedition, an unrecognized species of Stigmatodactylus was documented on the Marai Parai plateau on the flanks of Mt. Kinabalu. The taxon could not be keyed to any described species and is here presented as new, bringing the total number of Stigmatodactylus species known from Malaysia to three, and representing only the second species known from the island of Borneo. Fresh plant material was collected with authorization from Sabah Biodiversity Centre and Sabah Parks: (Access License JKM/MBS.1000-2/4/1(336); Invitation Letter Ref.-TTS/IP/900-0/11). Standard herbarium methods were used to prepare voucher specimens (Bridson and Forman 1998) and, for spirit collection, fresh samples were preserved in a solution consisting of 70% ethanol, 28% water and 2% glycerol. Both collections were deposited in the Sabah Parks Herbarium (SNP). The preserved flowers were dissected and photographed under an AM4113ZT Dino-Lite Digital Microscope.